2009
DOI: 10.1007/s00442-009-1350-9
|View full text |Cite
|
Sign up to set email alerts
|

Experimental confirmation of multiple community states in a marine ecosystem

Abstract: Small changes in environmental conditions can unexpectedly tip an ecosystem from one community type to another, and these often irreversible shifts have been observed in semi-arid grasslands, freshwater lakes and ponds, coral reefs, and kelp forests. A commonly accepted explanation is that these ecosystems contain multiple stable points, but experimental tests confirming multiple stable states have proven elusive. Here we present a novel approach and show that mussel beds and rockweed stands are multiple stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 57 publications
4
76
0
Order By: Relevance
“…When an ecosystem crosses a threshold or tipping point, its capacity to adapt to and cope with disturbances has been exhausted, and it abruptly reorganizes into a new regime with new structures, functions, and processes. Thresholds have been assessed in, for instance, intertidal marine ecosystems switching from rock weed beds to mussel stands (Petraitis et al 2009) or the encroachment of woody plants into grasslands as a function of fire intensity (Twidwell et al 2013). Scale Ecosystem structure is compartmentalized by spatial and temporal scales (Levin 1998), which can be assessed objectively using statistical tools ).…”
Section: Adaptive Capacitymentioning
confidence: 99%
“…When an ecosystem crosses a threshold or tipping point, its capacity to adapt to and cope with disturbances has been exhausted, and it abruptly reorganizes into a new regime with new structures, functions, and processes. Thresholds have been assessed in, for instance, intertidal marine ecosystems switching from rock weed beds to mussel stands (Petraitis et al 2009) or the encroachment of woody plants into grasslands as a function of fire intensity (Twidwell et al 2013). Scale Ecosystem structure is compartmentalized by spatial and temporal scales (Levin 1998), which can be assessed objectively using statistical tools ).…”
Section: Adaptive Capacitymentioning
confidence: 99%
“…Similarly, the timing of disturbance events with respect to seasonal period can determine their effects on biological responses (Nystrom et al 2000). Understanding spatiotemporal context can help to reconcile differences among case studies illustrating general types of transitions and state changes (e.g., Petraitis et al 2009). Contextual information also can help translate scientific analyses into meaningful policy recommendations and management interventions (Carpenter et al 2011).…”
Section: A Common Framework For Describing State Changementioning
confidence: 99%
“…They demonstrated that these effects translated into changes in adult densities and divergent successional patterns (Petraitis & Dudgeon 2005, Methratta & Petraitis 2008) and that some areas that were seaweed stands are now becoming mussel beds (Petraitis et al 2009). There has been some discussion whether the thresholds in the mussel-seaweed system are an example of multiple states or 2 states under different levels of top-down control (Bertness et al 2002, Petraitis & Dudgeon 2004a), although Petraitis et al (2009) suggested how these 2 seemingly different views can be reconciled.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…abrupt regime shifts from corals to macroalgae in tropical systems, and from macroalgae to barrens or mussel beds in temperate systems, which result in changes in abundance of exploited fish stocks (Done 1992, Hare & Mantua 2000, Konar & Estes 2003, deYoung et al 2004, Paine & Trimble 2004, Mumby 2009, Petraitis et al 2009). Ecologists are especially interested in these sudden shifts because they are common in a variety of situations, often occur unexpectedly, and are difficult to reverse.…”
Section: Introductionmentioning
confidence: 99%